Action Research for community business development. Issue 1 (4th February 2014) - MacLeod, Greg
Abstract : Purpose: – The purpose of this paper is to introduce the idea of Action Research as a way of making academic research more relevant for social economic change. Design/methodology/approach: – This paper seeks a middle path by presenting a method for Action Research that is both scientific and that results in practical social-economic impact on a local society. The method is divided into 11 systematic steps. Findings: – The author has found that the method results in job creation and place-based economic development. Originality/value: – Usually social activists and academic professionals do not mix. This approach combines both theory and practice, which is unusual in university circles.